The Role of Emerging ICT in the Ports: Increasing Utilities According to Shared Decisions - Russo, Francesco; Musolino, Giuseppe (Frontiers in Future Transportation, 2021)
Geographical location, infrastructures, and services are the main consolidated pillars of a port in terms of its capacity to compete and cooperate with other ports. In the last years, a new pillar was identified: emerging technologies. Ports’ issues were initially solved with individual ICT solutions adopted by each decision-maker, which generated efficiencies in the three main port flows: cargo, information, and financial. However, new benefits and challenges are connected with the introduction of shared emerging ICT among decision-makers inside ports. The crucial issue concerns the fact that several decision-makers could share a decision about a single-port operation. Therefore, the effectiveness and efficiency of ports depend on how the interactions between the decision-makers are solved. Port operations are associated with movements (cargo) and transactions (information and financial) in a synchronic graph, which allows highlighting the role of emerging technologies in the modification of port operation generalized cost, considering the different decision-makers. The focal point concerns the building of a theoretical model using the formal equations of Transport System Models (TSMs) for the estimation of the cost for a Unit of Load (UL), e.g., a container traveling along a path, composed of a sequence of port operations, inside a port with and without emerging technologies. The proposed theoretical model provides the possibility of estimating ex ante the reduction of cost (port time of UL) given by introducing new technologies and a Port Community System (PCS). Different scenarios, considering some cases, ranging from the absence of ICT to the presence of a PCS, are compared, considering the different situations from a non-congested port to a congested one. The main results of the study and its novelty concern, on the one hand, the extension of TSMs to port systems, highlighting the problem of a non-single decision-maker (two or more) in some port operations and, on the other hand, the possibility of reducing the generalized cost (e.g., time) in the same operations in which there are concurrent decision-makers, through the use of an advanced PCS. The reported numerical example confirms the theoretical results. The work can be useful for researchers for port planners (e.g., port authorities) because it permits evaluating the utility for introducing shared emerging technologies using advanced PCS in a unified view.